The Effects of Feeding Black Soldier Fly (Hermetia illucens) Maggot Meal as a Substitute for Fish Meal on Broiler Meat Quality - Mlaga , G.K.; Agboka, K.; Attivi, K.; Oke, O.; Osseyi, E.; Ameyapoh, Y.; Teteh, A.; Adjrah, Y.; Onagbesan, O.; Tona, K. (International Journal of Poultry Science, 2020)
Background and Objective: There has been a search for non-conventional feedstuffs such as maggot meal as a result of scarcity and high cost of fishmeal. The objective of this study was to evaluate the effect of the black soldier fly maggot meal as a protein source on meat quality of broiler chickens. Materials and Methods: A total of 225 broiler chicks (Ross 308) were assigned to five treatment groups of varying dietary inclusion levels of fish and maggot meal; 100% fishmeal and 0% maggot meal (control group) (A0), 75% fishmeal: 25% maggot meal (A25), 50% fishmeal: 50% maggot meal (A50), 25% fishmeal: 75% maggot meal A(75) and 100% maggot meal and 0% fishmeal (A100). At the 57th day, 6 chickens per replicate were randomly selected and slaughtered to evaluate the carcass yield and meat quality. Results: Results showed that there was a reduction of breast water loss in group A100 compared to the other batches (p